Los cuentos musicales para la estimulación de la creatividad de los niños de preparatoria de la Unidad Educativa del Milenio Canchagua cantón Saquisilí, provincia Cotopaxi. - Masapanta Masapanta, Diana Lisbeth (2025)
This research arises from the problem identified in high school children of the Millennium Educational Unit Canchagua, Saquisili canton, province of Cotopaxi, where there is evidence of a limited stimulation of creativity in the teaching-learning process. This deficit could be due to the lack of innovative methodologies that promote the development of imagination and divergent thinking in children. The main objective is to analyze the impact of musical stories on the stimulation of creativity in high school children. To theoretically support the study, a theoretical framework is established based on contributions from various authors and reliable sources, where topics related to stories, children's creativity, and musical methods are addressed. Special emphasis is given to Dalcroze's and Kodály's approaches, which emphasize the importance of music as a pedagogical tool to enhance children's cognitive and expression. The study population consisted of 16 high school children to whom the Torrance test was applied to evaluate their creativity before and after the intervention with musical stories. The application of 3 different tests revealed a deficit in creative stimulation within the educational context, reaffirming the need to strengthen pedagogical strategies. The results show that musical stories stimulate creativity and enhance children's expressive motor and socioemotional skills in children, improving the fluency, flexibility, and originality of creative thinking. We propose designing and implementing a manual, "Musical Strategies for the Stimulation of Creativity in High School Children," aimed at teachers as a methodological resource to enhance integral development in a dynamic and innovative environment.